Utilization of a new approach for the potassium concentration of sugarcane vinasse by reverse osmosis: case study - Silva, G. A.; Ferreira, S. L. [UNESP]; de Souza, G. R.; da Silva, J. A.; Pagliuso, J. D. (Springer Nature, 2019)
Ethanol is an alternative fuel produced from sugarcane and economically very important for São Paulo state and Brazil. Vinasse, which has been traditionally distributed on the agricultural soil as an organic fertilizer, is the main residue of the ethanol production. Its dosage has been annually rationed in function of the potassium balance for reuse in agriculture. The vinasse potassium for ferti-irrigation can fully substitute potassium from mineral sources, but its transport is economically unviable from a determined distance. In this context, the paper presents the dehydration of sugarcane vinasse using a reverse osmosis technology to reduce the cost of transport until the sugarcane tillage. The main contributions are the reduction in the water content (concentration) and increase in the solid and the potassium content (13.8%). The study showed a payback value of 5.49 years.
Keywords: Potassium; Reduce transport costs; Reverse osmosis; Sugarcane; Vinasse arrangement